Coal gasification ash water dispersant and preparation method thereof
By using modified hyperbranched polymers and modified polyacrylic acid, the problems of water pollution and equipment corrosion in the prior art are solved, and excellent dispersion, scale resistance and corrosion inhibition effects are achieved.
Patent Information
- Application Number
- CN202410726616.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-06-06
AI Technical Summary
The existing gasified ash water dispersants have problems of water pollution and equipment corrosion during use, and it is difficult to effectively prevent scaling and corrosion of equipment and pipelines.
Modified hyperbranched polymer and modified polyacrylic acid as main raw materials were used to prepare a coal gasified ash water dispersant with excellent dispersion, scale inhibition and corrosion inhibition through specific synthesis steps.
This dispersant can significantly improve the dispersion of scale-forming substances in gray water, prevent them from agglomeration and deposition, reduce the risk of corrosion of the equipment, and extend the service life of the equipment.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of industrial water treatment, and in particular to a coal gasification ash water dispersant and a preparation method thereof. Background Art
[0002] Coal gasification ash water dispersant is a chemical substance specially used to treat ash water and prevent scaling of equipment and pipelines in the coal gasification process. In the coal gasification process, ash water usually has the characteristics of high hardness, high turbidity, high alkalinity, etc., which is easy to form sediment, scaling and corrosion inside the equipment, thus affecting the normal operation and life of the equipment. Therefore, it is necessary to treat the ash water so that the main scaling substances in the ash water can be evenly dispersed in the aqueous solution. The commonly used ash water treatment method is to add a dispersant to make the scaling substances in the aqueous solution evenly dispersed and no longer aggregate and deposit, so as to achieve the purpose of scale inhibition.
[0003] At present, commonly used dispersants include phosphorus-containing polymers, copolymer dispersants, etc. However, the addition of phosphorus-containing polymers will cause water pollution and is rarely used. Phosphorus-free dispersants are mainly used to achieve scale inhibition. When using copolymer dispersants, the negatively charged ions in the copolymer can be chemically combined or physically adsorbed with the main scale-forming ions (calcium ions, magnesium ions) in the aqueous solution to make them evenly dispersed in the aqueous solution; substances and groups with corrosion inhibition can also be introduced into the copolymer to protect the metal surfaces inside the pipeline and equipment and extend the service life. Therefore, researchers need to develop a gray water dispersant with excellent dispersibility, scale inhibition and corrosion inhibition. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a coal gasification ash water dispersant and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A coal gasification ash water dispersant comprises the following raw materials in percentage by mass: 30%-50% of a modified hyperbranched polymer, 20%-40% of a modified polyacrylic acid, 5%-10% of sodium citrate, and the balance being water;
[0007] The modified hyperbranched polymer is prepared by the following steps:
[0008] Step A1, dispersing ethylenediamine in methanol to form a mixed solution, then slowly adding methyl acrylate using a constant pressure dropping funnel, and stirring at room temperature for 36-48 hours, then raising the system temperature to 50-60°C, reacting under vacuum conditions for 1-2 hours, maintaining the vacuum conditions, and continuing to heat to 85-95°C for reaction for 2-3 hours, and then heating again to 120-130°C for reaction for 3-4 hours. After the reaction is completed, distill under reduced pressure, add methanol to dilute, and then add ether and stir for 30 minutes. After standing, collect the lower layer and rotary evaporate to obtain a hyperbranched precursor;
[0009] Step A2, adding the hyperbranched precursor and sodium hydroxide to ethanol and mixing and stirring evenly, then adding epichlorohydrin and stirring for 2-3 hours, after the reaction is completed, distilling under reduced pressure, then slowly adding 24wt% sodium hydroxide solution dropwise, and heating to 80°C, reacting for 3 hours, after the reaction is completed, filtering, washing, and vacuum drying to obtain an epoxy-terminated hyperbranched polymer;
[0010] Step A3, adding succinic acid, terminal epoxy hyperbranched polymer and tetrabutylammonium bromide to N,N-dimethylformamide, stirring and mixing evenly, heating to 90° C. under nitrogen, and continuing the reaction for 5 hours. After the reaction is completed, rotary evaporation is performed, and then diluted with ethyl acetate, washed, dried, and rotary evaporation is performed to obtain a modified hyperbranched polymer;
[0011] Further, in step A1, the ratio of the mixed solution, methyl acrylate, methanol and diethyl ether is 30 mL: 0.1-0.2 mol: 50 mL: 200 mL, and the ratio of ethylenediamine and methanol in the mixed solution is 0.1-0.2 mol: 30 mL;
[0012] Further, in step A2, the usage ratio of the hyperbranched precursor, sodium hydroxide, ethanol, epichlorohydrin and sodium hydroxide solution is 0.01-0.02 mol: 0.005-0.015 mol: 50 mL: 0.1-0.2 mol: 20-30 mL;
[0013] Furthermore, in step A3, the usage ratio of succinic acid, terminal epoxy hyperbranched polymer, tetrabutylammonium bromide, N,N-dimethylformamide and ethyl acetate is 0.08-0.12 mol: 0.01 mol: 0.003-0.005 mol: 50 mL: 20 mL.
[0014] The modified polyacrylic acid is prepared by the following steps:
[0015] Step B1, adding sodium alginate, triethylamine and aluminum chloride into tetrahydrofuran and mixing and stirring evenly, then slowly dropping acryloyl chloride tetrahydrofuran solution, reacting in an ice-water bath with stirring for 5-8 hours, after the reaction is completed, filtering and distilling to obtain modified sodium alginate;
[0016] Step B2, adding sodium allyl sulfonate, acrylic acid, modified sodium alginate and potassium persulfate into a flask, stirring and mixing evenly, heating to 50-70° C. under nitrogen, maintaining the temperature for reaction for 12 hours, adding ethanol after the reaction is completed, adjusting the pH to 6.5-7, and then filtering, washing and drying to obtain modified polyacrylic acid;
[0017] Further, in step B1, the dosage ratio of sodium alginate, triethylamine, aluminum chloride, tetrahydrofuran and acryloyl chloride tetrahydrofuran solution is 0.01-0.02 mol: 10-20 g: 0.005-0.01 mol: 100 mL: 20 mL, and the dosage ratio of acryloyl chloride and tetrahydrofuran in the acryloyl chloride tetrahydrofuran solution is 6-7 g: 20 mL;
[0018] Furthermore, in step B2, the usage ratio of sodium allyl sulfonate, acrylic acid, modified sodium alginate, potassium persulfate and ethanol is 1-2 g: 12-16 g: 2-4 g: 0.15-0.25 g: 50 mL.
[0019] A method for preparing a coal gasification ash water dispersant comprises the following steps:
[0020] The raw materials are weighed according to mass percentage, and the modified hyperbranched polymer, modified polyacrylic acid, sodium citrate and deionized water are added into a stirrer, and stirred and mixed evenly to obtain a coal gasification ash water dispersant.
[0021] Beneficial effects of the present invention:
[0022] The coal gasification ash water dispersant prepared by the invention is composed of the following raw materials: modified hyperbranched polymer, modified polyacrylic acid, sodium citrate and deionized water; in the modified hyperbranched polymer, a Michael addition reaction between an amino group in ethylenediamine and a double bond in methyl acrylate is firstly used to synthesize a hyperbranched precursor containing a terminal amino structure; then, a ring-opening reaction is carried out by using the terminal epoxy group in the hyperbranched precursor and the epoxy group on epichlorohydrin, and under alkaline conditions, chloromethyl and hydroxyl groups in the product react to generate new epoxy groups, thereby obtaining a terminal epoxy hyperbranched polymer; finally, a carboxyl group in succinic acid reacts with an epoxy group in the terminal epoxy hyperbranched polymer to generate A modified hyperbranched polymer containing hydroxyl groups and terminal carboxyl groups; the branched structure of the modified hyperbranched polymer makes it have very high dispersibility in aqueous solution. After being dissolved in water, the branched chains extend in water. The negatively charged groups such as hydroxyl groups and carboxyl groups contained in the branched chain structure can adsorb calcium carbonate and calcium sulfate crystals in the aqueous solution. The adsorbed crystals will generate electrostatic repulsion between each other, thereby preventing the crystals from contacting each other, thereby preventing the formation of large crystals. At the same time, the crystals are uniformly dispersed in the aqueous solution due to being adsorbed by the branched chain structure, preventing the agglomeration of scaling ions, reducing the formation of crystal nuclei, and thus making scaling substances such as calcium carbonate and magnesium carbonate stably dispersed in gray water. Modified polyacrylic acid is firstly produced by reacting the carboxyl group in sodium alginate with the acyl chloride group in acryloyl chloride to introduce double bonds into sodium alginate to generate modified sodium alginate; then, under the initiation of potassium persulfate, sodium allyl sulfonate, acrylic acid and modified sodium alginate are polymerized to generate modified polyacrylic acid; modified polyacrylic acid is produced by using acrylic acid as the main synthetic monomer, sodium allyl sulfonate and modified sodium alginate as secondary monomers, and has good dispersibility, can effectively disperse particles in water, prevent the aggregation and deposition of particles, and is conducive to the uniform distribution of suspended matter, and can also utilize the negatively charged carboxyl group in the aqueous solution to disperse particles. Acid ions and sulfonate ions combine with hard water ions such as calcium and magnesium to prevent the formation of scale; the sodium alginate grafted in the modified polyacrylic acid has excellent water solubility, adsorption, non-toxicity, and environmental protection. Introducing it into polyacrylic acid improves the scale inhibition effect of the matrix in gray water. This is because sodium alginate can form complexes with calcium and magnesium ions in gray water and stably disperse them in aqueous solution, thereby effectively preventing the formation of wall scale. At the same time, it can also form a protective film with the metal surface to prevent metal corrosion and has a certain corrosion inhibition effect, thereby protecting the metal surface of equipment or pipelines and extending the service life. The addition of sodium citrate can make the solid particles in the gray water evenly dispersed in the solution, improve the stability and uniformity of the solution, and it can interact with the particle surface to reduce the attraction between particles and avoid the formation of large particles. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] The modified hyperbranched polymer is prepared by the following steps:
[0026] Step A1, 0.1 mol of ethylenediamine was dispersed in 30 mL of methanol to form a mixed solution, and then 0.1 mol of methyl acrylate was slowly added dropwise using a constant pressure dropping funnel, and stirred at room temperature for 36 hours, and then the system temperature was raised to 50° C., and reacted under vacuum conditions for 1 hour, and the vacuum conditions were maintained, and the temperature was further raised to 85° C. for reaction for 2 hours, and then the temperature was raised to 120° C. for reaction for 3 hours. After the reaction was completed, it was distilled under reduced pressure, 50 mL of methanol was added to dilute, and then 200 mL of ether was added and stirred for 30 minutes. After standing, the lower layer was collected and rotary evaporated to obtain a hyperbranched precursor;
[0027] Step A2, adding 0.01 mol of hyperbranched precursor and 0.005 mol of sodium hydroxide to 50 mL of ethanol, mixing and stirring evenly, then adding 0.1 mol of epichlorohydrin and stirring for 2 h. After the reaction is completed, distilling under reduced pressure, then slowly adding 20 mL of 24 wt% sodium hydroxide solution, and heating to 80° C., reacting for 3 h. After the reaction is completed, filtering, washing, and vacuum drying to obtain an epoxy-terminated hyperbranched polymer;
[0028] Step A3, add 0.08 mol of succinic acid, 0.01 mol of terminal epoxy hyperbranched polymer and 0.003 mol of tetrabutylammonium bromide to 50 mL of N,N-dimethylformamide, stir and mix evenly, raise the temperature to 90°C under nitrogen, and continue the reaction for 5 hours. After the reaction is completed, rotary evaporate, dilute with 20 mL of ethyl acetate, wash, dry, and rotary evaporate to obtain a modified hyperbranched polymer.
[0029] Modified polyacrylic acid is prepared by the following steps:
[0030] Step B1, add 0.01 mol sodium alginate, 10 g triethylamine, and 0.005 mol aluminum chloride into 100 mL tetrahydrofuran, mix and stir evenly, then slowly dropwise add 20 mL acryloyl chloride tetrahydrofuran solution, react for 5 h in an ice-water bath with stirring, after the reaction is completed, filter and distill to obtain modified sodium alginate, the amount ratio of acryloyl chloride to tetrahydrofuran in the acryloyl chloride tetrahydrofuran solution is 6 g: 20 mL;
[0031] Step B2, add 1g of sodium allyl sulfonate, 12g of acrylic acid, 2g of modified sodium alginate and 0.15g of potassium persulfate into a flask and stir to mix evenly. Under nitrogen conditions, heat to 50°C and maintain the temperature for 12h. After the reaction is completed, add 50mL of ethanol and adjust the pH to 6.5. Then filter, wash and dry to obtain modified polyacrylic acid.
[0032] Example 2
[0033] The modified hyperbranched polymer is prepared by the following steps:
[0034] Step A1, 0.15 mol of ethylenediamine was dispersed in 30 mL of methanol to form a mixed solution, and then 0.15 mol of methyl acrylate was slowly added dropwise using a constant pressure dropping funnel, and stirred at room temperature for 42 hours, and then the system temperature was raised to 55° C., and reacted under vacuum conditions for 1.5 hours, and the vacuum conditions were maintained, and the temperature was further raised to 90° C. for reaction for 2.5 hours, and then the temperature was raised to 125° C. for reaction for 3.5 hours. After the reaction was completed, it was distilled under reduced pressure, 50 mL of methanol was added to dilute, and then 200 mL of ether was added and stirred for 30 minutes. After standing, the lower layer was collected and rotary evaporated to obtain a hyperbranched precursor;
[0035] Step A2, adding 0.015 mol of hyperbranched precursor and 0.01 mol of sodium hydroxide to 50 mL of ethanol and mixing and stirring evenly, then adding 0.15 mol of epichlorohydrin and stirring for 2.5 h, after the reaction is completed, distilling under reduced pressure, then slowly adding 25 mL of 24 wt% sodium hydroxide solution, and heating to 80° C., reacting for 3 h, after the reaction is completed, filtering, washing, and vacuum drying to obtain an epoxy-terminated hyperbranched polymer;
[0036] Step A3, add 0.1 mol of succinic acid, 0.01 mol of terminal epoxy hyperbranched polymer and 0.004 mol of tetrabutylammonium bromide to 50 mL of N,N-dimethylformamide, stir and mix evenly, raise the temperature to 90°C under nitrogen, and continue the reaction for 5 hours. After the reaction is completed, rotary evaporate, dilute with 20 mL of ethyl acetate, wash, dry, and rotary evaporate to obtain a modified hyperbranched polymer.
[0037] Modified polyacrylic acid is prepared by the following steps:
[0038] Step B1, add 0.05 mol sodium alginate, 15 g triethylamine, and 0.0075 mol aluminum chloride into 100 mL tetrahydrofuran, mix and stir evenly, then slowly dropwise add 20 mL acryloyl chloride tetrahydrofuran solution, react for 6 hours under ice-water bath and stirring conditions, after the reaction is completed, filter and distill to obtain modified sodium alginate, the amount ratio of acryloyl chloride to tetrahydrofuran in the acryloyl chloride tetrahydrofuran solution is 6.5 g: 20 mL;
[0039] Step B2, add 1.5g sodium allyl sulfonate, 14g acrylic acid, 3g modified sodium alginate and 0.2g potassium persulfate into a flask and stir to mix evenly. Under nitrogen conditions, heat to 60°C and maintain the temperature for 12h. After the reaction is completed, add 50mL of ethanol and adjust the pH to 6.8. Then filter, wash and dry to obtain modified polyacrylic acid.
[0040] Example 3
[0041] The modified hyperbranched polymer is prepared by the following steps:
[0042] Step A1, 0.2 mol of ethylenediamine was dispersed in 30 mL of methanol to form a mixed solution, and then 0.2 mol of methyl acrylate was slowly added dropwise using a constant pressure dropping funnel, and stirred at room temperature for 48 hours, and then the system temperature was raised to 60°C, and reacted under vacuum conditions for 2 hours, and the vacuum conditions were maintained, and the temperature was further raised to 95°C for reaction for 3 hours, and then the temperature was raised to 130°C for reaction for 4 hours. After the reaction was completed, it was distilled under reduced pressure, 50 mL of methanol was added to dilute, and then 200 mL of ether was added and stirred for 30 minutes. After standing, the lower layer was collected and rotary evaporated to obtain a hyperbranched precursor;
[0043] Step A2, adding 0.02 mol of hyperbranched precursor and 0.015 mol of sodium hydroxide to 50 mL of ethanol, mixing and stirring evenly, then adding 0.2 mol of epichlorohydrin and stirring for 3 h. After the reaction is completed, distilling under reduced pressure, then slowly adding 30 mL of 24 wt% sodium hydroxide solution, and heating to 80° C., reacting for 3 h. After the reaction is completed, filtering, washing, and vacuum drying to obtain an epoxy-terminated hyperbranched polymer;
[0044] Step A3, add 0.12 mol of succinic acid, 0.01 mol of terminal epoxy hyperbranched polymer and 0.005 mol of tetrabutylammonium bromide to 50 mL of N,N-dimethylformamide, stir and mix evenly, raise the temperature to 90°C under nitrogen, and continue the reaction for 5 hours. After the reaction is completed, rotary evaporate, dilute with 20 mL of ethyl acetate, wash, dry, and rotary evaporate to obtain a modified hyperbranched polymer.
[0045] Modified polyacrylic acid is prepared by the following steps:
[0046] Step B1, add 0.02 mol sodium alginate, 20 g triethylamine, and 0.01 mol aluminum chloride into 100 mL tetrahydrofuran, mix and stir evenly, then slowly dropwise add 20 mL acryloyl chloride tetrahydrofuran solution, react for 8 h in an ice-water bath with stirring, after the reaction is completed, filter and distill to obtain modified sodium alginate, the amount ratio of acryloyl chloride to tetrahydrofuran in the acryloyl chloride tetrahydrofuran solution is 7 g: 20 mL;
[0047] Step B2, add 2g of sodium allyl sulfonate, 16g of acrylic acid, 4g of modified sodium alginate and 0.25g of potassium persulfate into a flask and stir to mix evenly. Under nitrogen conditions, heat to 70°C and maintain the temperature for 12h. After the reaction is completed, add 50mL of ethanol and adjust the pH to 7. Then filter, wash and dry to obtain modified polyacrylic acid.
[0048] Example 4
[0049] A method for preparing a coal gasification ash water dispersant comprises the following steps:
[0050] 30% of the modified hyperbranched polymer prepared in Example 1, 40% of the modified polyacrylic acid prepared in Example 1, 10% of sodium citrate, and the balance of water;
[0051] The raw materials were weighed according to mass percentage, and the modified hyperbranched polymer prepared in Example 1, the modified polyacrylic acid prepared in Example 1, sodium citrate and deionized water were added into a stirrer and stirred and mixed evenly to obtain a coal gasification ash water dispersant.
[0052] Example 5
[0053] A method for preparing a coal gasification ash water dispersant comprises the following steps:
[0054] 40% of the modified hyperbranched polymer prepared in Example 2, 30% of the modified polyacrylic acid prepared in Example 2, 8% of sodium citrate, and the balance of water;
[0055] The raw materials were weighed according to the mass percentage, and the modified hyperbranched polymer prepared in Example 2, the modified polyacrylic acid prepared in Example 2, sodium citrate and deionized water were added into a stirrer, and stirred and mixed evenly to obtain a coal gasification ash water dispersant.
[0056] Example 6
[0057] A method for preparing a coal gasification ash water dispersant comprises the following steps:
[0058] 50% of the modified hyperbranched polymer prepared in Example 3, 25% of the modified polyacrylic acid prepared in Example 3, 10% of sodium citrate, and the balance of water;
[0059] The raw materials were weighed according to mass percentage, and the modified hyperbranched polymer prepared in Example 3, the modified polyacrylic acid prepared in Example 3, sodium citrate and deionized water were added into a stirrer, and stirred and mixed evenly to obtain a coal gasification ash water dispersant.
[0060] Comparative Example 1
[0061] This comparative example is a ash water dispersant, which differs from Example 6 in that an equal amount of a hyperbranched polymer prepared by the following method is used to replace the modified hyperbranched polymer prepared in Example 3, and the rest are the same;
[0062] Hyperbranched polymers are prepared by the following steps:
[0063] 0.2 mol of ethylenediamine was dispersed in 30 mL of methanol to form a mixed solution, and then 0.2 mol of methyl acrylate was slowly added dropwise using a constant pressure dropping funnel, and stirred at room temperature for 48 hours, and then the system temperature was raised to 60°C, and reacted under vacuum conditions for 2 hours. The vacuum conditions were maintained, and the temperature was further raised to 95°C for reaction for 3 hours, and then the temperature was raised to 120°C for reaction for 4 hours. After the reaction was completed, it was distilled under reduced pressure, 50 mL of methanol was added to dilute, and then 200 mL of ether was added and stirred for 30 minutes. After standing, the lower layer was collected and rotary evaporated to obtain a hyperbranched polymer;
[0064] Comparative Example 2
[0065] This comparative example is a ash water dispersant, which is different from Example 6 in that the modified polyacrylic acid prepared in Example 3 is replaced by an equal amount of polyacrylic acid prepared by the following method, and the rest are the same;
[0066] Polyacrylic acid is prepared by the following steps:
[0067] Add 22g of acrylic acid and 0.25g of potassium persulfate into a flask and stir to mix evenly. Under nitrogen, heat to 70°C and maintain the temperature for 12h. After the reaction is completed, add 50mL of ethanol and adjust the pH to 7. Then filter, wash and dry to obtain modified polyacrylic acid.
[0068] The grey water dispersants prepared in Examples 4-6 and Comparative Examples 1-2 were added to grey water to perform performance tests:
[0069] Scale inhibition rate: tested in accordance with HG / T2024-2009 standard;
[0070] Corrosion performance test: The rotating coupon corrosion performance test was carried out in accordance with GB 50050-2017 standard; the test results are shown in the following table:
[0071] Scale inhibition rate (%) Corrosion rate (mm / a) Example 4 93.6 0.0028 Example 5 94.3 0.0027 Example 6 96.2 0.0025 Comparative Example 1 86.8 0.0035 Comparative Example 2 87.9 0.0043
[0072] It can be seen from the above table that the ash water dispersant prepared by the present invention has an excellent scale inhibition rate and can significantly reduce the corrosion rate.
[0073] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A coal gasification ash water dispersant, characterized in that: The invention comprises the following raw materials in percentage by weight: 30%-50% of modified hyperbranched polymer, 20%-40% of modified polyacrylic acid, 5%-10% of sodium citrate, and the balance of water; The modified hyperbranched polymer is prepared by the following steps: Step A1, dispersing ethylenediamine in methanol to form a mixed solution, then slowly adding methyl acrylate using a constant pressure dropping funnel, and stirring at room temperature for 36-48 hours, then raising the system temperature to 50-60°C, reacting under vacuum conditions for 1-2 hours, maintaining the vacuum conditions, and continuing to heat to 85-95°C for reaction for 2-3 hours, and then heating again to 120-130°C for reaction for 3-4 hours. After the reaction is completed, distill under reduced pressure, add methanol to dilute, and then add ether and stir for 30 minutes. After standing, collect the lower layer and rotary evaporate to obtain a hyperbranched precursor; Step A2, adding the hyperbranched precursor and sodium hydroxide to ethanol and mixing and stirring evenly, then adding epichlorohydrin and stirring for 2-3 hours, after the reaction is completed, distilling under reduced pressure, then slowly adding 24wt% sodium hydroxide solution dropwise, and heating to 80°C, reacting for 3 hours, after the reaction is completed, filtering, washing, and vacuum drying to obtain an epoxy-terminated hyperbranched polymer; Step A3, add succinic acid, terminal epoxy hyperbranched polymer and tetrabutylammonium bromide to N,N-dimethylformamide, stir and mix evenly, raise the temperature to 90°C under nitrogen, and continue the reaction for 5 hours. After the reaction is completed, rotary evaporate, dilute with ethyl acetate, wash, dry and rotary evaporate to obtain a modified hyperbranched polymer.
2. A coal gasification ash water dispersant according to claim 1, characterized in that: In step A1, the usage ratio of the mixed solution, methyl acrylate, methanol and diethyl ether is 30 mL: 0.1-0.2 mol: 50 mL: 200 mL, and the usage ratio of ethylenediamine and methanol in the mixed solution is 0.1-0.2 mol: 30 mL.
3. A coal gasification ash water dispersant according to claim 1, characterized in that: In step A2, the usage ratio of the hyperbranched precursor, sodium hydroxide, ethanol, epichlorohydrin and sodium hydroxide solution is 0.01-0.02 mol: 0.005-0.015 mol: 50 mL: 0.1-0.2 mol: 20-30 mL.
4. The coal gasification ash water dispersant according to claim 1, characterized in that: In step A3, the usage ratio of succinic acid, terminal epoxy hyperbranched polymer, tetrabutylammonium bromide, N,N-dimethylformamide and ethyl acetate is 0.08-0.12 mol: 0.01 mol: 0.003-0.005 mol: 50 mL: 20 mL.
5. The coal gasification ash water dispersant according to claim 1, characterized in that: Modified polyacrylic acid is prepared by the following steps: Step B1, adding sodium alginate, triethylamine and aluminum chloride into tetrahydrofuran and mixing and stirring evenly, then slowly dropping acryloyl chloride tetrahydrofuran solution, reacting in an ice-water bath with stirring for 5-8 hours, after the reaction is completed, filtering and distilling to obtain modified sodium alginate; Step B2, add sodium allyl sulfonate, acrylic acid, modified sodium alginate and potassium persulfate into a flask and stir to mix evenly, raise the temperature to 50-70°C under nitrogen, maintain the temperature for 12 hours, add ethanol after the reaction is completed, adjust the pH to 6.5-7, then filter, wash and dry to obtain modified polyacrylic acid.
6. A coal gasification ash water dispersant according to claim 5, characterized in that: In step B1, the dosage ratio of sodium alginate, triethylamine, aluminum chloride, tetrahydrofuran and acryloyl chloride tetrahydrofuran solution is 0.01-0.02 mol: 10-20 g: 0.005-0.01 mol: 100 mL: 20 mL, and the dosage ratio of acryloyl chloride and tetrahydrofuran in the acryloyl chloride tetrahydrofuran solution is 6-7 g: 20 mL.
7. The coal gasification ash water dispersant according to claim 5, characterized in that: In step B2, the dosage ratio of sodium allyl sulfonate, acrylic acid, modified sodium alginate, potassium persulfate and ethanol is 1-2 g: 12-16 g: 2-4 g: 0.15-0.25 g: 50 mL.
8. The method for preparing a coal gasification ash water dispersant according to claim 1, characterized in that: The following steps are involved: The raw materials are weighed according to mass percentage, and the modified hyperbranched polymer, modified polyacrylic acid, sodium citrate and deionized water are added into a stirrer, and stirred and mixed evenly to obtain a coal gasification ash water dispersant.
Citation Information
Patent Citations
Preparation method for highly effective maleic anhydride series polymer antisludging agent
CN101041516A
Method used for high efficiency adsorbing of heavy metals with functionalized magnetic material rich in thio amino groups
CN106395965A